Synthesis and characterization of polymeric materials and their applications in removal and recovery of heavy metals from industrial wastewater. - Ibrahim, Mahamad Hakimi
The transformation of fish bones and pomelo peels into adsorbents in order to remove and recover heavy metals from aqueous solution has been successfully undertaken. The physical and chemical characteristics of the powdered fish bones and pomelo peels were studied. The effect of pH, adsorbent dose, adsorbate concentration as well as adsorption mechanism were identified in this work.